'What if my Wi-Fi crashes during an exam?' First-year engineering student perceptions of online learning during the COVID-19 pandemic. (4th May 2022) - Howcroft, Jennifer; Mercer, Kate
ABSTRACT: The COVID-19 pandemic necessitated a rapid transition to remote education in post-secondary institutions. To understand the first-year engineering undergraduate student perceptions of this transition to online learning, surveys were administered in two design-focused first-year engineering courses with a total of 201 enrolled students. A thematic qualitative analysis of open-ended survey questions resulted in 7 themes: Health & Safety, Growth Mindset, Student Agency, Course Design, Coping/Management, Execution, and Technology. Students expressed positive and negative perceptions of remote education and included opinions related to current and future learning, and future careers. Most student perceptions were grounded in fear of the unknown, and student mental health emerged as a predominant undercurrent in the data. The identified themes and underlying student perceptions suggest that instructors teaching online should aim to (1) support communication, collaboration, and student engagement, (2) promote meaningful learning and growth mindsets, and (3) foster strong learning partnerships and class experiences.